Effectiveness of Water Bamboo as Phytoremediation Agent BOD and COD Leachate - Ade Ihtiar; Maria Ulfah; Fibria Kaswinarni (Journal of Environmental and Science Education, 2024)
Leachate is  a liquid with an unpleasant odor and dark color that generally contains high organic and inorganic matter. High levels of organic and inorganic matter in leachate will potentially cause environmental pollution if not treated properly. One of the efforts that can be made to overcome these problems is with phytoremediation techniques. This study aims to determine the effectiveness of water bamboo (Equisetum hymale) as a phytoremediation agent  of Biological Oxygen Demand (BOD) and Chemical Oxygen Demand (COD) leachate of Jatibarang landfill. This study used experimental research with a one-factorial Complete Randomized Design (RAL) design with three treatments (P0 without water bamboo, P1 750 gr water bamboo, and P2 1000 gr water bamboo). Based on the results of research shows that water bamboo plants can reduce BOD and COD levels. The decrease in leachate BOD levels was caused by the phytoremediation process by water bamboo during the study, where the organic matter content in leachate would be degraded by microorganisms. Meanwhile, COD levels decreased due to the chemical oxidation reaction process and phytoremediation process that runs side by side. The effectiveness of reducing BOD levels most optimally occurred in treatment P2 on day 7 of treatment, which was 28.42%; while the percentage of effectiveness of reducing COD levels most optimally occurred in treatment P2 on day 7 of treatment, which was 39.14%